2012
DOI: 10.1038/bjc.2011.582
|View full text |Cite
|
Sign up to set email alerts
|

Irreversible electroporation on the small intestine

Abstract: Background:Non-thermal irreversible electroporation (NTIRE) has recently been conceived as a new minimally invasive ablation method, using microsecond electric fields to produce nanoscale defects in the cell membrane bilayer and induce cell death while keeping all other molecules, including the extracellular matrix, intact. Here, we present the first in vivo study that examines the effects of NTIRE on the small intestine, an organ whose collateral damage is of particular concern in the anticipated use of NTIRE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 41 publications
1
53
0
Order By: Relevance
“…Moreover, this process leads to the creation of nanopores with a disruption of the lipid bilayer and cell death, due to apoptosis, preserving the underlying extracellular matrix [5,6,7,8,9,10,11]. Consequently, IRE has begun to emerge as an important ablation technique, that unlike radiofrequency [12] and microwave or laser [13] does not require the application of thermal energy, thereby preserving sensitive structures located near the tumor, such as nerves, bile ducts, vessels, and the gastrointestinal tract [14,15,16]. …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this process leads to the creation of nanopores with a disruption of the lipid bilayer and cell death, due to apoptosis, preserving the underlying extracellular matrix [5,6,7,8,9,10,11]. Consequently, IRE has begun to emerge as an important ablation technique, that unlike radiofrequency [12] and microwave or laser [13] does not require the application of thermal energy, thereby preserving sensitive structures located near the tumor, such as nerves, bile ducts, vessels, and the gastrointestinal tract [14,15,16]. …”
Section: Introductionmentioning
confidence: 99%
“…These findings indicated that IRE could not only locally destroy the tumor but also change the status of cellular immunity in osteosarcoma-bearing rats [Li et al, 2012]. Some reports indicate that this novel procedure can be used for abdominal cancer treatment while minimising collateral damage to adjacent tissues because of the unique ability of the ablation method to target the cell membrane [Phillips et al, 2012]. Irreversible electroporation (IRE) is a new ablative technology that uses high-voltage, low-energy DC current to create nanopores in the cell membrane, disrupting the homeostasis mechanism and inducing cell death by initiating apoptosis in patients with Hepatocellular carcinoma (HCC) [Narayanan et al, 2013].…”
Section: Advantages Disadvantages and Solutionsmentioning
confidence: 98%
“…The results are taken from the study reported in [67] and show that (i) immediately after NTIRE the scaffold remains intact while the cells are ablated and (ii) seven days after the tissue ablation, endothelial cells and muscle cells begin to regenerate and form new villi (thin protuberances of the small intestine, through which digested food passes into the blood). The molecular selectivity of NTIRE may find additional applications in tissue engineering [68].…”
Section: Nonthermal Tissue Ablation By Means Of Irreversible Electropmentioning
confidence: 99%
“…Thus the activity of the immune system, which is connected to all parts of the ablated tissue through the large blood vessel scaffolds [63], is enhanced. Furthermore, the intact extracellular matrix facilitates regeneration of tissue in the liver [63], blood vessels [65], nerves [66], and small intestines [67].…”
Section: Nonthermal Tissue Ablation By Means Of Irreversible Electropmentioning
confidence: 99%